KEEFEKTIFAN MODEL CONTEXTUAL TEACHING LEARNING TERHADAP KOMPETENSI MENENTUKAN GAGASAN POKOK PARAGRAF TEMA 1 KELAS V SDN BANYUBIRU 01 KABUPATEN SEMARANG - Eko Nur Fatoni; Suyitno YP; Filia Prima Artharina (Universitas Ngudi Waluyo, 2020)
The background of this research is the low competence to determine the main ideas of paragraphs, where students still have difficulty determining the main ideas of paragraphs. The purpose of this study is to improve student learning outcomes through the use of Contextual Teaching Learning learning models. This study uses a pre-experimental method with the One Group Pretes-Posttes research design because it only uses one class, so researchers use this design in the hope that the results of the posttest will be better than the results of the achievement after the use of the Contextual Teaching Learning learning model. The data obtained from this study are in the form of posttest which is greater than the pretest and obtained a value of Lhitung 0, 166 with a significant level of 5%, n = 37 and obtained Ltable 0, 145. Because Lhitung <Ltable then 0.081 <0, 145 means that the data normally distributed, so the posttest value data comes from a sample of a normally distributed population. This means that the Contextua Teaching Learning model is effective on the competence of determining the main ideas of the fifth grade paragraphs of SDN Banyubiru 02 Semarang Regency.